2017
DOI: 10.1002/2016jg003641
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of the controlling factors of soil organic carbon and nitrogen densities in a permafrost-affected region on the eastern Qinghai-Tibetan Plateau

Abstract: Many investigations of the preservation of soil organic carbon (SOC) in permafrost regions have examined roles of geomorphology, pedogenesis, vegetation cover, and permafrost within particular regions. However, it is difficult to disentangle the effects of multiple factors on the SOC in permafrost regions due to the heterogeneity in environmental conditions. Based on data from 73 soil study sites in permafrost regions of the eastern Qinghai‐Tibetan Plateau, we developed a simple conceptual model, which relates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 72 publications
6
31
2
Order By: Relevance
“…The higher soil moisture may also be related to the higher clay contents in the permafrost areas, as fine particles have higher water holding capacities (Gómez‐Plaza et al, ). This result is consistent with the interactions among the permafrost and environmental factors (Wu et al, ). Specifically, the drainage conditions, which are affected by the geomorphology, determine plant growth.…”
Section: Discussionsupporting
confidence: 91%
“…The higher soil moisture may also be related to the higher clay contents in the permafrost areas, as fine particles have higher water holding capacities (Gómez‐Plaza et al, ). This result is consistent with the interactions among the permafrost and environmental factors (Wu et al, ). Specifically, the drainage conditions, which are affected by the geomorphology, determine plant growth.…”
Section: Discussionsupporting
confidence: 91%
“…Organic layers are mainly distributed in the alpine swamp meadow on the QTP (Hu et al,). The alpine desert steppe vegetation region stored much lower soil organic carbon contents than the other vegetation regions on the QTP (X. Wu et al, , ). The areas of alpine swamp meadows accounted for 4% of the permafrost areas on the QTP (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The areas of alpine swamp meadows accounted for 4% of the permafrost areas on the QTP (Wang et al, ). It was reported that there was almost no peat layer in the permafrost regions on the QTP (X. Wu et al, , ). Due to the relatively dry soil, the coarse soil materials, and the lack of winter snow cover over the QTP (Wu & Zhang, ), the effects of organic layers were not considered in our simulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher clay and silt contents favour plant growth because they have higher water holding capacity, and consequently increasing carbon input to soil (Yang et al, ). The soil texture, especially clay and silt fractions, and SM are the most important factors contributing to the variations in soil organic content on the QTP (Wu et al, ). Vegetation and SM mutually influence each other (Shang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation and SM mutually influence each other (Shang et al, ). Higher SM combined with lower soil temperature in the alpine swamp meadow may be associated with a lower decomposition rate, which in turn leads to higher soil organic matter content (Shang et al, ; Wu et al, ). For example, the higher soil organic carbon content assessed using laboratory measurements at QT03 may be explained by the higher SM (Shang et al, ).…”
Section: Discussionmentioning
confidence: 99%